U5 snRNA Interactions With Exons Ensure Splicing Precision - Artemyeva-Isman, Olga V.; Porter, Andrew C. G. (Frontiers in Genetics, 2021)
Imperfect conservation of human pre-mRNA splice sites is necessary to produce alternative isoforms. This flexibility is combined with precision of the message reading frame. Apart from intron-termini GU_AG and the branchpoint A, the most conserved are the exon-end guanine and +5G of the intron-start. Association between these guanines cannot be explained solely by base-pairing with U1snRNA in the early spliceosome complex. U6 succeeds U1 and pairs +5G in the pre-catalytic spliceosome, while U5 binds the exon-end. Current U5snRNA reconstructions by CryoEM cannot explain the conservation of the exon-end G. Conversely, human mutation analyses show that guanines of both exon-termini can suppress splicing mutations. Our U5 hypothesis explains the mechanism of splicing precision and the role of these conserved guanines in the pre-catalytic spliceosome. We propose: 1) Optimal binding register for human exons and U5 - the exon junction positioned at U5Loop1 C39|C38. 2) Common mechanism of base pairing of human U5snRNA with diverse exons and bacterial Ll.LtrB intron with new loci in retrotransposition - guided by base pair geometry. 3) U5 plays a significant role in specific exon recognition in the pre-catalytic spliceosome. Our statistical analyses show increased U5 Watson-Crick pairs with the 5’exon in the absence of +5G at the intron-start. In 5’exon positions -3 and -5 this effect is specific to U5snRNA rather than U1snRNA of the early spliceosome. Increased U5 Watson-Crick pairs with 3’exon position +1 coincide with substitutions of the conserved -3C at the intron 3’end. Based on mutation and X-ray evidence we propose that -3C pairs with U2 G31 juxtaposing the branchpoint and the 3’intron-end. The intron-termini pair, formed in the pre-catalytic spliceosome to be ready for transition after branching, and the early involvement of the 3’intron-end ensure that the 3’exon contacts U5 in the pre-catalytic complex. We suggest that splicing precision is safeguarded cooperatively by U5, U6 and U2snRNAs that stabilise the pre-catalytic complex by Watson-Crick base pairing. In addition, our new U5 model explains the splicing effect of exon-start +1G mutations: U5 Watson-Crick pairs with exon +2C/+3G strongly promote exon inclusion. We discuss potential applications for snRNA-therapeutics and gene repair by reverse splicing.